PENGARUH PENGGUNAAN ARTIFICIAL INTELIGENCE (AI) DALAM MENINGKATKAN KETERAMPILAN BERBAHASA DAN KEPENULISAN MAHASISWA PGMI UIN SULTAN THAHA SAIFUDDIN JAMBI - Arum Dwi Arum Asmi azizah (Jurnal Lazuardi, 2026)
This study aims to describe and analyze the influence of Artificial Intelligence (AI) on improving language skills and academic writing abilities of students in the Primary School Teacher Education Program (PGMI) at UIN Sultan Thaha Saifuddin Jambi. The research employed a qualitative approach with field research methods to obtain an in-depth understanding of students’ experiences, perceptions, and practices in utilizing AI in academic activities, particularly in writing processes and appropriate language use. Data were collected through observations, in-depth interviews, and documentation, with informants selected using purposive sampling, supported by course lecturers as additional informants. Data analysis was conducted through data reduction, presentation, and conclusion drawing, with data validity maintained using triangulation of sources and methods. The results indicate that AI functions as a mediator and digital scaffolding in the writing process, assisting students in organizing outlines, improving sentence structures, and conducting iterative revisions. AI provides fast and personalized linguistic feedback, enhancing students’ language awareness, self-confidence, efficiency, and creativity in producing academic writing. The study also shows that AI supports reflective learning and independent learning, although the development of critical analytical skills still requires additional pedagogical interventions. This research confirms that AI can strengthen students’ language and writing skills while emphasizing the need for responsible use of technology to maintain originality and academic quality.